2016
DOI: 10.1002/cncr.30119
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing for the risk of developing late effects among survivors of childhood cancer: Consumer understanding, acceptance, and willingness to pay

Abstract: BACKGROUND Genetic testing to determine cancer survivors' risk of developing late effects from their cancer treatment will be increasingly used in survivorship care. This 2‐stage study with 64 survivors of childhood cancer and their parents investigated the preferences and acceptability of testing among those who may be at risk of developing late effects. METHODS The first stage (Stage 1) identified the most commonly perceived benefits and concerns regarding genetic testing for the risk of late effects among 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…While willingness to pay was not the focus of our study, it is worth noting that patients in the United States and Australia have been shown to be willing to pay for genetic testing that is not covered by their insurance plans (Georgiou et al, ; Lin, Yeh, & Neumann, ; Marshall et al, ) and Canadians have been shown to be willing to pay for other healthcare services (Guimarães et al, ). However, if patients are not aware of this option, their willingness to pay becomes irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…While willingness to pay was not the focus of our study, it is worth noting that patients in the United States and Australia have been shown to be willing to pay for genetic testing that is not covered by their insurance plans (Georgiou et al, ; Lin, Yeh, & Neumann, ; Marshall et al, ) and Canadians have been shown to be willing to pay for other healthcare services (Guimarães et al, ). However, if patients are not aware of this option, their willingness to pay becomes irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…Four surveys were excluded for being filled out by young adult patients themselves or participants with an unknown relation to the patient. Questions were developed through discussion of prior literature and Institutional Review Board (IRB) suggestions regarding anonymity and passive collection to keep the survey simple 10,[25][26][27][28][29][30][31]35 (Supplemental Digital Content 1 for the survey, http://links.lww.com/JPHO/A490). This study was reviewed by the Johns Hopkins Medicine IRB and was deemed exempt.…”
Section: Methodsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] Parents also reported feeling that they had an inadequate level of genetics knowledge to understand CPS and that family counseling or educational material would be beneficial. 26,28,29 Therefore, genetic counseling may be a useful psychological and educational intervention for these families. Education of pediatric physicians and nurses to optimize familycentered and timely referrals in genetic medicine has the potential to improve patient care and outcomes.…”
mentioning
confidence: 99%
See 2 more Smart Citations